Class Collembola Lubbock, 1870. In: Zhang, Z.-Q. (Ed.) Animal biodiversity: An outline of higher-level classification and survey of taxonomic richness - Janssens, Frans; Christiansen, Kenneth A. (Zootaxa, 2011)
-